A general discussion on photon spheres in different categories of spacetimes - Chen-Kai Qiao; Ping Su; Yang Huang (European Physical Journal C: Particles and Fields)
Abstract Photon spheres have attracted considerable interest in the studies of black holes and other astrophysical objects. For different categories of spacetimes (or gravitational sources), the existence of photon spheres and their distributions are dramatically influenced by the geometric and topological properties of spacetimes and characteristics of the corresponding gravitational fields. In this work, we carry out a geometric analysis on photon spheres for different categories of spacetime (including black hole spacetime, ultra-compact object’s spacetime, regular spacetime, and naked singularity spacetime). Some universal properties and conclusions are obtained for these spacetimes. We mostly focus on the existence of photon spheres, the total number of photon spheres $$n = n_{\text {stable}} + n_{\text {unstable}}$$ n = n stable + n unstable , the subtraction of stable photon sphere and unstable photon sphere $$w = n_{\text {stable}} - n_{\text {unstable}}$$ w = n stable - n unstable in different categories of spacetimes. These conclusions are derived solely from geometric properties of optical geometry of spacetimes, irrelevant to the specific spacetime metric forms. Besides, our results successfully recover some important theorems on photon spheres proposed in recent years.